Coronavirus Disease (COVID-19–SARS-CoV-2) and Nutrition: Is Infection in Italy Suggesting a Connection? - Cena, Hellas; Chieppa, Marcello (Frontiers in Immunology, 2020)
The novel coronavirus outbreak (COVID-19) has been recognized as a pandemic on March 11 2020 after the exponential growth of infection started from China in December 2019 and severely hitting Italy in February 2020. Several countries are adopting complete or partial lockdown to contain the COVID-19 infection growth. This strategy, particularly if perpetuated for long periods, may have a negative impact for peoples’ health conditions. Based on data from the Italian and Chinese cohort, we underline the emerging concepts about a possible links between chronic inflammation COVID-19 mortality, particularly in fragile subject. Furthermore, we highlight nutritional behaviours that may help reducing the inflammatory cytokines secretion caused by COVID-19 infection.